Military Intervention via Drone Strikes - Rafat Mahmood; Michael Jetter (Institute of Labor Economics (IZA), 2019)
We study the 420 US drone strikes in Pakistan from 2006-2016, isolating causal effects on terrorism, anti-US sentiment, and radicalization via an instrumental variable strategy based on wind. Drone strikes are suggested to encourage terrorism in Pakistan, bearing responsibility for 16 percent of all attacks or 2,964 terror deaths. Exploring mechanisms, we distinguish between insiders (members of terrorist organizations) and outsiders (the Pakistani populace). Analyzing data from a leading Pakistani newspaper, anti-US protests, and Google searches, drone strikes appear to increase anti-US sentiment and radicalization: Outsiders seem to sympathize with insiders because of drone strikes.
Keywords: C26; D74; F51; F52; H56; O53; 330; military intervention; drone strikes; terrorism; counter-terrorism; anti-US sentiment; radicalization